Effects of interactions between variation in dopaminergic genes, traumatic life events, and anomalous self-experiences on psychosis proneness: Results from a cross-sectional study in a nonclinical sample. Issue 1 (20th November 2020) - Frydecka, Dorota; Kotowicz, Kamila; Gawęda, Łukasz; Prochwicz, Katarzyna; Kłosowska, Joanna; Rymaszewska, Joanna; Samochowiec, Agnieszka; Samochowiec, Jerzy; Podwalski, Piotr; Pawlak-Adamska, Edyta; Szmida, Elżbieta; Cechnicki, Andrzej; et al.
Abstract: Background: There is a growing number of studies showing interactions between genetic polymorphisms associated with dopaminergic neurotransmission and traumatic life events (TLEs) on a risk of psychotic-like experiences (PLEs). Anomalous self-experiences (ASEs) have been associated both with TLEs as well as with PLEs. However, it remains unknown what is the role of ASEs in the complexity of gene–environment interactions on the emergence of PLEs. Patients and methods: We included 445 young adults—university students from three big cities in Poland. We used the Traumatic Events Checklist to assess TLEs, the Inventory of Psychotic-Like anomalous self-experiences in order to measure ASEs, and the Prodromal Questionnaire (PQ16) to record the level of PLEs. The following gene polymorphisms, related to dopaminergic neurotransmission, were determined: the catechol- O -methyltransferase ( COMT ) rs4680 polymorphism, the dopamine D2 receptor ( DRD2 ) rs6277 polymorphism, and the dopamine transporter 1 ( DAT1 ) rs28363170 polymorphism. Results: There was a significant effect of the interaction between the DAT1 polymorphism, a severity of ASEs, and a history of TLEs on the level of PLEs. Among the DAT1 10R/10R homozygotes with low level of ASEs, a severity of PLEs was significantly higher in individuals with a history of any TLEs. Higher scores of the PQ16 were associated with a greater severity of ASEs both in the DAT1 9R allele carriers and the DAT1 10R/10R homozygotes. Conclusion: Our findings imply that genetic liability related to aberrant dopamine transport might impact the association between TLEs and PLEs in subjects with high levels of ASEs.